IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LEARNING COMMUNITY UNDER CONTEXTUAL TEACHING AND LEARNING APPROACH (An Experimental Study at the Second Year of SMA Negeri 2 Bandar Baru) - Mustakim Sagita (Jurnal Sains Riset, 2017)
Reading is a part of language skills that needs to be increased by the students. Learning Community is used. It invites the students to read, think, predict, and prove each paragraph in narrative text. It employs collaborative Action Research and subjects of the research are 27 students. The criteria of success including: students are active and happy, the students’ reading ability improves, and 80% students can achieve the passing grade of the reading comprehension in English lesson that is 75. The finding indicates that CTL Strategy could improve the students’ ability in reading comprehension of narrative text. Key Words: CTL, Learning Community (LC), reading comprehension, narrative text.